Cadangan reka bentuk subsistem maklumat perundangan bagi pengurusan kawasan tanah bencah kajian kes: Tg. Piai & Sg. Pulai - Hosni, Nafisa (2006)
Wetland are among the most important and productive ecosystems in the world as it provide critical nesting, rearing, feeding and stop over habitat for bird and other wildlife populations in the wet condition. These wetland’s functions are thus extremely valuable whereby management about their use should be made with great caution. The wetland management processes involve the technique of systematic compilation of analysis and evaluation of environmental and ecological attributes of the wetland. It requires a systematic management system in ensuring that the decisions made are based on the relevant guidelines before any action taken. Therefore, the management activities mainly involves proposed development exercised by Johor National Park Corporation as an approving authority in management planning area should be guided by laws and other mechanism such as policies, acts, regulations and guidelines. It is found that, the guidelines as references for management processes are still in manual form (paper basis). The references involve stack of papers with vary types of guidelines and acts caused the difficulties of referencing for management purposes. Even though the existing acts and regulations are there and being accepted but the implementation of it is still far from satisfactory and inefficient. The issues and problems invite study to be conducted whereby Tanjung Piai and Sungai Pulai Mangrove Reserve are chosen as study area. In making the laws and guidelines much easier to refer, this study has proposed translation of guidelines into spatial data context. In this study, the relevant legislations are analyzed based on the spatial and activities implication. This study has identified three (3) main stages of analysis i.e. determination of biosphere zones, determination of zoning plan and legislation’s implication. The conducted analysis proposes a design of Legislation Information Subsystem (LIS). This study, proposed three (3) main modules of LIS namely Physical Condition, Management Planning and Legislation References. It is hoped that, the manifestation of legislation into spatial data through GIS application and together with the proposed Legislation Information Subsystem will facilitate and assist manager in managing their own area and eventually will enhance and improving the use of existing legislation in the management system.